2022
DOI: 10.1111/1753-6405.13304
|View full text |Cite
|
Sign up to set email alerts
|

Support‐seeking by cancer caregivers living in rural Australia

Abstract: Objective: Rural cancer caregivers report poor wellbeing and high unmet needs for support. This study investigates sources of support sought by cancer caregivers living in rural Australia, and factors associated with support-seeking.Methods: Informal caregivers of people with cancer completed a questionnaire assessing sociodemographic characteristics, caregiver factors and support-seeking. Descriptive statistics, bivariate analyses and logistic regression were used to identify common sources of support and fac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 38 publications
0
7
0
Order By: Relevance
“…They proposed the development of adapted, and culturally appropriate interventions (i.e., which go beyond deficits‐based perspectives that focus on stigma and self‐reliance as barriers) and instead recognise and draw upon rural strengths such as resilience and community networks. In Australia, rural cancer caregivers report accessing support for the person they are supporting less commonly than they access support for themselves 43 . Considering this alongside the systemic barriers experienced by those in rural areas, and our finding that patients value their informal supports, it may be relevant to streamline support for rural cancer patients and those who support them.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…They proposed the development of adapted, and culturally appropriate interventions (i.e., which go beyond deficits‐based perspectives that focus on stigma and self‐reliance as barriers) and instead recognise and draw upon rural strengths such as resilience and community networks. In Australia, rural cancer caregivers report accessing support for the person they are supporting less commonly than they access support for themselves 43 . Considering this alongside the systemic barriers experienced by those in rural areas, and our finding that patients value their informal supports, it may be relevant to streamline support for rural cancer patients and those who support them.…”
Section: Discussionmentioning
confidence: 93%
“…In Australia, rural cancer caregivers report accessing support for the person they are supporting less commonly than they access support for themselves. 43 Considering this alongside the systemic barriers experienced by those in rural areas, and our finding that patients value their informal supports, it may be relevant to streamline support for rural cancer patients and those who support them. Culturally responsive interventions for rural cancer patients are also salient in Australia, 30 where many rural cancer patients travel to metropolitan areas to receive treatment outside of a familiar context.…”
Section: Discussionmentioning
confidence: 97%
“…Tis paper uses data from a longitudinal cohort study, Travelling for Treatment, that tracked patient-reported outcome measures across time (up to 5 years from study recruitment). Data from this study have been reported in several other publications [17][18][19][20]. Recruitment for the Travelling for Treatment study was conducted between September 2017 and June 2020.…”
Section: Methodsmentioning
confidence: 99%
“…Previous research has also identified that if post‐treatment information needs are not met in healthcare settings, cancer survivors look elsewhere for this information, particularly from online or interpersonal sources that may not be credible or accurate 8,9 . For example, 30%–40% of rural cancer survivors and their caregivers report referring to online sources from support 10,11 . In the case of online content on diet and exercise for cancer survivors, reviews have shown that advice is often unverified, incomplete, inaccurate or not up to date which could lead to patient harm 8,9 .…”
Section: Introductionmentioning
confidence: 99%
“…8,9 For example, 30%-40% of rural cancer survivors and their caregivers report referring to online sources from support. 10,11 In the case of online content on diet and exercise for cancer survivors, reviews have shown that advice is often unverified, incomplete, inaccurate or not up to date which could lead to patient harm. 8,9 Thus, meeting the information needs of cancer survivors is vital for ensuring quality survivorship care and wellbeing.…”
Section: Introductionmentioning
confidence: 99%